2008
DOI: 10.2165/0151642-200815040-00001
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the i-SEARCH Global Study

Abstract: Microalbuminuria (MAU) is a highly predictive, sensitive, inexpensive and easily repeatable marker of cardiovascular risk and all-cause mortality in hypertensive patients. The international, observational, practice-based study i-SEARCH (Survey for Evaluating Microalbuminuria Routinely by Cardiologists in patients with Hypertension) was designed to assess the frequency with which MAU occurred in a large outpatient population who were currently treated or newly diagnosed with hypertension and were under professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…The reported prevalence of microalbuminuria in our study is comparable to what has been reported in one large international multi-center study [ 17 ] and in other African hypertensive populations [ 16 , 18 , 19 ]. In the international, observational, practice-based study i-SEARCH (Survey for Evaluating Microalbuminuria Routinely by Cardiologists in patients with Hypertension) that was designed to assess the frequency with which microalbuminuria occurred in a large outpatient population of 21,050 patients who were currently treated or newly diagnosed with hypertension and were under professional care in 26 countries, a high overall prevalence of microalbuminuria of 58.4 % noted [ 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…The reported prevalence of microalbuminuria in our study is comparable to what has been reported in one large international multi-center study [ 17 ] and in other African hypertensive populations [ 16 , 18 , 19 ]. In the international, observational, practice-based study i-SEARCH (Survey for Evaluating Microalbuminuria Routinely by Cardiologists in patients with Hypertension) that was designed to assess the frequency with which microalbuminuria occurred in a large outpatient population of 21,050 patients who were currently treated or newly diagnosed with hypertension and were under professional care in 26 countries, a high overall prevalence of microalbuminuria of 58.4 % noted [ 17 ].…”
Section: Discussionsupporting
confidence: 90%